Socio-Economic Conditions of Unemployed Urban Youths: Evidence from Dilla and Yirgacheffe Towns of Gedeo Zone - Kebede, Olira; Leta, Belayneh (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2019)
In Ethiopia, youth unemployment is becoming a more pressing issue. Scholarly works in the area have exhaustively studied the prominent causes of youth unemployment. By going beyond the causes, this article critically examines the social and economic conditions of unemployed urban youths in the study areas. The researchers have employed qualitative research approach. The study has used both primary and secondary data sources to produce a full-fledged research article. In-depth interview, focus group discussion and naturalistic observation were the instruments through which primary data were collected. Relevant books, journal articles, magazines, official document and research works were consulted as the principal sources of secondary data. The researchers purposively selected 42 key informants and 12 participants of focus group discussions in the study areas. Unemployed youth are facing many social and economic problems including, social exclusion, low self-confidence, carelessness, low saving, mental and physical disease and fear. As a result, some of them were forced to commit crime and drink alcohol. These problems affected the physical, emotional and psychological lives of unemployed youth in the study areas. The study investigated that town administrations took some measures to reduce youth unemployment in the study areas through organizing youth into groups, providing them certain trainings and encouraging them for job creation. However, they were unable to reduce youth unemployment due to the imbalance between number of unemployed youths and job availability, insufficient labor market and financial problems. Finally, in order to address the social and economic problems of unemployed youth in the study areas this article has suggested the following recommendations: enhancing awareness of the communities and youths, building industrial zones in the study areas, promoting youth entrepreneurs and self-employment, providing long and Short term training for unemployed youths, and making convenient business climate for unemployed youths.